Disaster Management and Risk Reduction: Multidisciplinary Perspectives and Approaches in the Indian Context Proceedings of NERC 2022 - Mitra, Sudip; Dasgupta, Kaustubh; Dey, Arindam; Bedamatta, Rajshree (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book presents select proceedings of North-East Research Conclave (NERC 2022) that will help pave way toward disaster risk reduction through a holistic and multidisciplinary approach. The book discusses topics, such as rapid pace of climate change, its deleterious effects on nature and natural systems, human interventions in altering the natural geographical and geological systems, widespread urbanization, recurrent unwarranted rainfall and cloud bursts, unprecedented flooding, catastrophic landslides, dam breakages, glacial outbursts, snow avalanches, seismicity and its impacts, liquefaction, and wreaking environmental pollution leading to unimaginable toll on lives, property and economy. The book also discusses approaches to address such issues and frame a refined path towards a sustainable future, such as a three-fold approach like - Awareness, Inferences and Implementations. For this approach, it is ardently necessary to understand the core reasoning behind the disasters, their impact on the socio-economic contexts, and the ways to mitigate them. The book can be a valuable reference for beginners, researchers, and professionals interested in disaster risk reduction and allied fields.
Landslide Early Warning and Susceptibility Zonation of Guwahati City through Local and Regional Scale Slope Stability Analyses -- Structural and Geotechnical Approach of Characterisation of the Causes of Meriema Landslide along the Kohima - Wokha Road Section of the National Highway No. 61, near Nagaland University-Kohima Campus Approach Road Junction, Nagaland, India -- Assessment and Analysis of Geotechnical Properties of Saron Veng Landslide, Aizawl, Mizoram -- Impact Of Heavy Precipitation On Landslide Due To Climate Change And Probable Remedial Measure -- Landslide Susceptibility Mapping Using Machine Learning Algorithm.
Keywords: Engineering geology; Geotechnical engineering; Bioclimatology; Sociology, Urban; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Climate Change Ecology; Urban Sociology